The state of parental involvement in the education of ECD learners at two schools in the Disosi schools cluster of Tsholotsho District - Ngwenya, Proud (Midlands State University, 2020)
The study investigated the state of parental involvement in the education of ECD learners in the DISOSI schools cluster of Tsholotsho District. The study was aimed at investigating the forms in which parents are involved, the structures that enhance parental involvement in the cluster, challenges faced as a result of parental involvement and the strategies that enhance parental involvement. Data were collected through the use of interviews for parents and questionnaires for ECD teachers and School administrators (Heads and T.I.Cs). A sample of 13 ECD teachers, 25 parents and 4 school administrators was selected. Purposive sampling was used for teachers and administrators while convenient sampling was used for parents. Case study was used. Data were presented through the use of frequency tables, graphs and descriptions. Findings show that parents are not fully active in some of the forms of parental involvement. Recommendations for enhancement of parental involvement were offered based on the findings of the study.